GLUT1‐mediated glucose uptake plays a crucial role during Plasmodium hepatic infection. (2nd August 2016) - Meireles, Patrícia; Sales‐Dias, Joana; Andrade, Carolina M.; Mello‐Vieira, João; Mancio‐Silva, Liliana; Simas, J. Pedro; Staines, Henry M.; Prudêncio, Miguel
Summary: Intracellular pathogens have evolved mechanisms to ensure their survival and development inside their host cells. Here, we show that glucose is a pivotal modulator of hepatic infection by the rodent malaria parasite Plasmodium berghei and that glucose uptake via the GLUT1 transporter is specifically enhanced in P . berghei ‐infected cells. We further show that ATP levels of cells containing developing parasites are decreased, which is known to enhance membrane GLUT1 activity. In addition, GLUT1 molecules are translocated to the membrane of the hepatic cell, increasing glucose uptake at later stages of infection. Chemical inhibition of GLUT1 activity leads to a decrease in glucose uptake and the consequent impairment of hepatic infection, both in vitro and in vivo . Our results reveal that changes in GLUT1 conformation and cellular localization seem to be part of an adaptive host response to maintain adequate cellular nutrition and energy levels, ensuring host cell survival and supporting P . berghei hepatic development.